EVALUATION OF SOIL PHYSICAL PROPERTY AS A DETERMINING FACTOR OF EROSION: A CASE STUDY OF BEHIND NIGERIA INSTITUTE OF LEATHER AND SCIENCE TECHNOLOGY, ZARIA (FUDMA JOURNAL OF SCIENCES, 2021)
Soil Erosion is the detachment, transportation and deposition of soil sediment from one place to another. This has led to loss of lives and infrastructure in many parts of Nigeria. Soil properties play a role in it vulnerability and extent to erosion. This study aims to evaluate selected physical properties as they interact to cause erosion in the study area.  The study was conducted in 2012 in a gully site in relation to its potential to erodibility of gully channel. This was done by collection of various soil samples at different depth followed by laboratory analysis to determine the plastic limit, moisture content and other engineering properties. The Results indicated that the soil samples have Atterberg limit that might be considered low, while liquid limit (LL) ranged from 25 â€“ 30, the plasticity index (PI) ranged from 1 â€“ 5%, which suggested that the soils are slightly plastic. Moisture content was moderate. The soil properties investigated played a major role in exacerbating the gully erosion in the area, therefore, the existing culvert should be redesigned and reconstructed taking appropriate consideration of the underlying soil properties
Keywords: Samaru, Gully, Erosion and Soil properties